(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
During the Covid-19 pandemic, learning in Indonesia was carried out online or e-learning. There are many negative perceptions of students, lecturers and society towards e-learning in general. The purpose of this study is to analyze the perceptions of students, lecturers and the community to-wards e-learning based on dalihan na tolu. This research method is a quantitative and qualitative descriptive method that aims to describe the situation objectively. The sample of this research is 40 students and 32 lecturers of Tarutung State Institute for Christian Studies who have experienced the e-learning process for two years. The perception data of lecturers and students were obtained by using a questionnaire. In addition, as many as 13 people, as parents of elementary, middle and high school students, were interviewed to obtain data on public perceptions of dalihan na tolu - based e-learning. The results showed that the perceptions of students, lecturers and society. E-learning based on dalihan na tolu tends to be more effective in improving the learning process and outcomes compared to the random/conventional system.